An Investigation of the Effectiveness of Cognitive Behavioral Therapy and Methadone Treatment on Quality of Life, Cravings Management, and Psychological Distress in Individuals Abstaining from Drugs - امیرتورج پورنژدی; جعفر حسنی; شهرام محمدخانی (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2017)
Aim and Background: Substance use disorder (SUD) is one of main issues in the field of mental health and can have negative consequences for patients as well as their families and the society in which they live. The purpose of this study was the investigation of the effectiveness of cognitive behavioral therapy (CBT) and methadone treatment on quality of life (QOL), cravings management, and psychological distress in individuals abstaining from drugs. Methods and Materials: This research was implemented using the multiple baseline experimental design within the framework of a single-subject research. Based on the study inclusion criteria, 4 patients were selected using convenience sampling and assigned to the CBT and methadone treatment groups. Individuals in the methadone treatment group received their medication in accordance to the prescription of a physician and those in the CBT group underwent 12 sessions of CBT for addiction. All participants completed the quality of life questionnaire, craving beliefs questionnaire, Beck Depression Inventory (BDI), and Beck Anxiety Inventory (BAI) at certain intervals. Findings: Given the visual inspection of charts, effect size, indicators of improvement, and reduction in scores, CBT was more effective than methadone treatment in increasing QOL (effects size of -0.9 versus -0.62) and reducing depression symptoms (effect size of 0.92 versus 0.78). However, both treatment methods were equally effective in reducing craving (effect size of 0.84 versus 0.74) and anxiety symptoms (effect size of 0.86 versus 0.87). Conclusions: It can be concluded that CBT can decrease psychological distress and cravings and improve QOL through thinking structure modification.